PEMILIHAN GENTENG RUMAH MENGGUNAKAN METODE MULTIDIMENSIONAL SCALING - Edwin Prihatin; Andi Nur Rahman (LPPM Universitas Bina Bangsa, 2022)
Tile is one of the most important building materials. Tile has the main function as a roof covering. Tile is more often used in the construction of houses. The tile protects the occupants of the house from the hot sun and rain. Selection of the right tile needs to be considered for the comfort of the occupants of the house. In this study, the determining factors in the selection of roof tiles are price, product quality, and product availability. The types of tiles used in this research are ceramic tiles, clay tiles, Alderon tiles, asbestos tiles, zinc tiles, and metal roof tiles. The method used in this study is the multidimensional scaling method. The multidimensional scaling method is one of the multivariate analysis methods used to determine the similarity value based on the proximity seen on the perceptual map. Based on the calculation results, it is determined that the types of tiles that have similarities are ceramic tiles and Alderon tiles with a distance value of 0.2062. Furthermore, the best roof tiles based on respondents' perceptions are Asbestos tiles because the variables of product quality and product availability have advantages